About a French engineer's judgement on the Abbey of Middelburg in 1812. The Abbey of Middelburg, a caricature of architecture? (Bulletin KNOB, 1990)
In 1810 the province of Zealand became a part of the great French empire and was officially named 'Département des Souches de l'Escaut' (Departement of the Mouthes of the Scheldt) with Middelburg as its capital. A prefecture had to be set up here and the old seat of the former centre of government, the Abbey in Middelburg, was considered the best site for it. Napoleon attached great value to architectural provisions (mainly for military purposes) because of the strategic importance of this department. However, there was no local architect to meet the new requirements and who could cooperate with the French experts at their level.Paris immediately understood the necessity of sending an all-round architect to Middelburg. Special emphasis was laid on military demands and those of the Navy in particular. Nicolas Jean-Baptiste Anselin was appointed on 1 March 1812. At the Ecole Polytechnic in Paris he had received the best architectural education the French empire could offer in the beginning of the 19th century. The original centre of government in the former Province of Zealand in no way answered the needs of a rational modern administration, and offices in accordance with them. The representative function and the high standing of the department were also of importance.Anselin was commissioned to reconstruct the Abbey, then still an example of mediaeval architecture, so as to make it suitable to serve as a palace for the prefect on the one hand and as the administrative centre of the prefecture on the other. His designs and the accompanying reports, sent to Paris by the prefect, were based on the newest French ideas on architecture and his ideas are reflected in his writings on the subject. Indeed, the subtitle of this very article is borrowed from one of his statements. The designs were for the extensive Abbeycomplex to be updated as much as possible, in accordance with the ideas of Anselin's teacher Durand. The enterprise was never realised after all because of the short duration of the Napoleon government. Nevertheless from the architectural point of view it is important to get acquainted with the new ideas that inspired it.